Strengthening Mental Health Literacy Character Education at Smpit Permata Insani - Supini; Alia Nabilah; Dea Puspita Aurellia; Via Octaviani; Octaviana Sitorus; Arif Budi Sunjaya; Muhidin Muhamad Jaelani; Helen Rizki Amalia; Hijrat, Abdullah; Rumi Arny Ompusunggu; Maya Fharsita Putri; Galuh Kumara (Jurnal Pengabdian Masyarakat Formosa, 2024)
Literacy is a person's ability to read and write, which contributes to the formation of a student's character. Health is defined as a condition in which a person can overcome challenges to achieve happiness both in this world and in the afterlife, which can be influenced by each person's character. Character is something that comes naturally to everyone. Family, school and society are some of the factors that shape a person's character, not innate character. This article presents the results of Community Service activities with the theme "Strong Literacy, Healthy Mentality!" at SMPIT Permata Insani. This activity aims to strengthen character education through literacy and mental health. Held on November 18 2024, this activity involved 11 students from the Management Study Program at Panca Sakti University, Bekasi, with a work program to disseminate material and create a reading corner. It is hoped that students can improve their understanding of literacy and maintain mental health. This activity also aims to provide solutions to social problems and improve the quality of education at SMPIT Permata Insani.